The implementation of life cycle costing towards private client’s investment: the case of Malaysian construction projects - Norhanim Zakaria,; Azlan Shah Ali,; Umi Kalsum Zolkafli, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Life-cycle Costing (LCC) is a technique used to estimate the total cost of ownership. It allows comparative cost assessments to be made over a specific period of time, taking into account relevant economic factors both in terms of initial capital costs and future operational and asset replacement cost. The implementation of LCC in construction industry is rapidly increasing. However, in the Malaysian construction industry, LCC has not been implemented extensively. This paper explored LCC implementation in construction projects in Malaysia from the client’s perspective as well as benefits and barriers to implementing LCC. A quantitative approach involving questionnaire survey distributed to private clients in the Malaysian construction industry. More than half of the surveyed respondents indicated they were ready to invest in future costs and about 37% were currently implementing LCC or a similar costing principle. The inability of LCC to meet expectations of organisation in managing costs, lack of familiarity with LCC and the market not requiring the use of LCC were the main reason why organisations who had used LCC in the past discontinued the use of LCC. Influencing future costs in the design stage, greater emphasis on achieving a better ‘value for money’ in projects and improving awareness of total cost of projects were the three major benefits of implementing LCC while lack of a procurement and contract award incentives to use LCC, lack of a standard method of LCC, and clients’ unwillingness to pay for LCC were identified as the main barriers to implementing LCC. Correlation analysis demonstrated that implementation of LCC during ‘investment planning’, ‘scheme/concept design’, ‘detail/final design’, ‘construction and commission’, and ‘operation and maintenance’ stages had statistically significant relationship with ‘quality performance’, while implementing LCC ‘investment planning’, ‘scheme/concept design’, ‘detail/final design’, and ‘operation and maintenance’ stages significantly correlated with ‘overall project performance’. The importance of LCC in various project stages, the study concludes by emphasizing the need to create more awareness and implementation methodology to promote the adoption of LCC in the Malaysian construction industry.